أثر الاستثمار الأجنبي المباشر على ميزان المدفوعات في سورية خلال الفترة (2000_2010) - صقر, محمد; شيحا, مضر (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يشهد العالم بدايةً من النصف الثاني من القرن العشرين توجهاً متزايداً نحو الاستثمارات الأجنبية المباشرة باعتبارها أداة تنموية فاعلة. ولاسيما بعد ظهور النظريات التنموية الحديثة القائمة على فكرة مفادها أن عجز التنمية في البلدان النامية لا يعود إلى عدم توفر متطلبات التنمية من موارد اقتصادية مادية بل يعود إلى عجز تلك البلدان عن رسملة مواردها واستغلالها بالشكل الذي يجعل منها محركاً للنمو ودافعاً له باتجاه تحقيق التنمية الاقتصادية الشاملة ويشكل هذا النوع من الاستثمار أحد أهم المرتكزات الاقتصادية في الواقع المعاصر, إذ أنه يلعب دوراً هاماً على صعيد عملية التنمية الاقتصادية والاجتماعية لدى الدول ذلك لكونه قناة رئيسة يتدفق عبرها رأس المال والتكنولوجيا المتطورة والمهارات الإدارية. فقد بدأ الاستثمار الأجنبي المباشر يلعب دوراً كبيراً في دعم نمو اقتصاديات الدول النامية منذ ثمانينيات القرن الماضي مستفيداً من الانتشار السريع لتكنولوجيا المعلومات والاتصالات والاتجاه نحو اقتصاد السوق في معظم الدول النامية وتحرير التجارة فيها, وازداد اعتماد هذه الدول على الاستثمار الأجنبي المباشر نظراً للمنافع الكبيرة التي تجنيها منه, سواءً من ناحية تكوين رأس المال وتوليد فرص العمل وزيادة الصادرات, أو من ناحية الحصول على التكنولوجيا الحديثة اللازمة لتحقيق التنمية الاقتصادية. كما يعتبر أداة هامة للتسريع بعمليات التصنيع وتطوير البنية التحتية مما يجعل له آثاراً على ميزان المدفوعات من حيث قدرته على التأثير في الحساب الجاري والحساب الرأسمالي وبالتالي في وجود إمكانية لاستخدامه كأداة في تحسين وضع ميزان المدفوعات للدول النامية ومنها سورية. فقد بدأت تدفقات الاستثمار الأجنبي المباشر الوارد إلى سورية بالتزايد منذ عام 2003م وذلك نتيجة التوجهات الجديدة للحكومة السورية نحو الانفتاح على القطاع الخاص المحلي والأجنبي والاعتماد على اقتصاد السوق. سيحاول هذا البحث معرفة أثر تدفقات هذا النوع من الاستثمارات على وضع ميزان المدفوعات السوري من خلال تأثيرها على كل من الحساب الجاري والحساب الرأسمالي والمالي خلال الفترة 2000_2010م, نظراً لعدم توافر الإحصائيات المطلوبة خلال سنوات الأزمة الحالية. In the second half of the 20th century, the world witnessed an increasing trend towards foreign direct investment as an effective development tool. Especially after the emergence of modern development theories based on the idea that the development deficit in developing countries is not due to the lack of development requirements of material economic resources, but due to the inability of these countries to capitalize resources and exploit them in such a way that makes them an engine of growth and motivation towards achieving Comprehensive economic development This type of investment is one of the most important economic pillars in contemporary reality, as it plays an important role in the process of economic and social development in countries, because it is a major channel flow through capital and advanced technology and skills Administration. FDI has played a major role in supporting the growth of the economies of developing countries since the 1980s, taking advantage of the rapid spread of ICTs , the trend towards a market economy in most developing countries and trade liberalization. In terms of capital formation, jobs generation and export expansion, or in terms of access to modern technology needed for economic development. It is also an important tool for accelerating the processes of manufacturing and infrastructure development, which affects the balance of payments due to its ability to affect the current account and the capital account, therefore there is possibility to use it as a tool to improve the balance of payments situation of developing countries, including Syria. FDI inflows into Syria have been increasing since 2003 as a result of the Syrian government's new approach to openness to the domestic and foreign private sector and adaptation of a market economy. This study will attempt to determine the effect of the flows of this type of investment on the Syrian balance of payments situation through its impact on both the current account and the capital and financial account during the period 2000_2010. Because the required statistics are not available for current crisis period .